THE WANING POWER. AN ANALYSIS OF CONTEMPORARY FRENCH DEFENSE POLICY (Journal of the Spanish Institute for Strategic Studies, 2018)
The article analyzes the evolution of French defense policy from the Cold Warto the present day. After presenting the country’s strategic outlook during theCold War, the article studies the White Papers drawn up by France to adaptits national defense and military organization to the changing domesticand international situation. Viewed as a whole, they show the profoundtransformations French defense policy has experienced over the last decades